The Rohingya refugee crisis and Bangladesh-Myanmar relations - Othman, R. (2013)
The Rohingya refugee crisis is a contentious issue that has strained Myanmar- Bangladesh relations since the late 1970s. The Rohingya crisis emanated from the military junta’s widespread violations of human rights in Myanmar against the Rohingya Muslims in Rakhine. Rendered stateless, the Rohingyas fled to Bangladesh and other neighboring countries to take refuge. Years of negotiation have failed to resolve the Rohingya refugee crisis. This research note proposes the need for intensive bilateral and multilateral negotiations, a prospect which is likely to be facilitated by the process of democratization in Myanmar.